(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
This study entitled “Empowering Students to Engage with Media and Communication” is a field study conducted on a sample of primary school teachers in Algeria. Media education has become a modern necessity aimed at developing students and enhancing their abilities to optimally engage with media, which now constitutes a cultural and cognitive background for students. With the immense development of media and communication technology, many concepts have changed, including the concept of educational media, which initially referred to learning from the media. This concept has evolved to include warnings about its dangers (”defence”) and has now shifted to include empowerment. However, the contradiction and conflict between the school system and the media system persists, leaving this concept shrouded in ambiguity. While we await a serious consideration of this concept and its adoption in our schools within a clear strategy, the importance of media literacy is widely acknowledged. Nevertheless, this concept remains largely absent in Algerian schools, resulting in a limited role for teachers, who engage in personal initiatives in the classroom, mainly focused on awareness and guidance, as the results of this study show.